Strategi Pengembangan Wisata Edukasi pada Candi Sambisari di Kabupaten Sleman - Putri, Pipiet Arini; Sri Giriwati, Novi Sunu; Yusran, Yusfan Adeputera; Santosa, Herry (RUAS, 2023)
There is a shift in tourist interest in an environmentally friendly tour, including interest in educational tourism. Tourists are more interested in natural scenery and the lack of interest in historical tourism is an obstacle for Sambisari Temple, especially if it is seen as a site of historical and cultural value, Sambisari Temple has the potential to be developed into educational tourism. This study aims to recommend educational tourism development strategies in educational tourism of Sambisari Temple. Data analysis was carried out with descriptive techniques on the potential of Sambisari Temple. In the next stage, a SWOT analysis is carried out. The result is that the development strategy can be carried out by conducting periodic checks on buildings and areas around the temple, especially during the rainy season, involving tourists in the learning process in making tour packages, providing space for tourists to explore attractions accompanied by a tour guide, promoting temple educational tours through websites or social media, establishing more intensive cooperation and collaboration with the government,  improve the quality and quantity of visitor facilities, create a mini museum and other supporting facilities such as ATMs in the Sambisari Temple complex.